From scaffold to structure: the synthetic production of cell derived extracellular matrix for liver tissue engineering. (17th October 2018) - Grant, Rhiannon; Hay, David; Callanan, Anthony
Abstract: Liver transplant is the only curative treatment option for patients with end-stage liver failure, however there are few donor livers available for transplant. Tissue engineering of a human liver would potentially solve the problem of escalating donor shortages. A major challenge presents itself in the form of the hepatic extracellular matrix (ECM); a finely controlled in vivo niche which supports hepatocytes and plays a critical role in the development of liver disease. Polymers and decellularized tissues each provide some of the necessary biological cues for the hepatocytes, however, neither alone has proved sufficient. Equally, the ability to fine tune the microenvironment using bioactive molecules presents researchers with the opportunity to create personalised niches for hepatocytes, representing both normal and diseased phenotypes. This study combines cell derived ECM with a fibronectin vector and electrospun scaffolding techniques to produce a platform for creating customisable ECM microenvironments for hepatocytes (Abstract image). The resulting poly-L-lactic acid-extracellular matrix (PLA-ECM) scaffolds were validated using HepG2 hepatocytes. As expected, statistically significant mechanical differences were observed between the synthetically derived ECM (SD-ECM) scaffolds and normal ECM (N-ECM) scaffolds, confirming that the ECM has been altered by the fibronectin producing vector. The PLA-ECM scaffolds maintained hepatocyte growth and function and influence the gene expression of key hepatic genes. Furthermore, immunohistochemistry showed SD and N-ECMs differed in ratios of Collagen I, Laminin and Fibronectin. Our results demonstrate that hybrid PLA-ECM scaffolds and the synthetic production of ECM provide a viable, translatable platform for customising microenvironments for hepatocytes. This technology offers a potential solution to current obstacles in regenerative medicine, disease modelling and whole organ tissue engineering.